Complexation of metal ions by benzylidenepyruvate, in aqueous solution - Siqueira, Onofre Salgado; Melios, Cristo Bladimiros; Redigolo, Helena; Ionashiro, Massao; Molina, Manuel (Eclética Química, 1991)
.